2021
DOI: 10.1360/tb-2021-0902
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-conjugated <sup>10</sup>B<sub>4</sub>C nanoparticles: Preparation and application in combined boron neutron capturetherapy/chemotherapy

Abstract: 网络版发表 放射医学与辐射防护国家重点实验室创新项目(GZC00102)资助 摘要 硼中子俘获治疗(boron neutron capture therapy, BNCT)是一种二元靶向肿瘤治疗 方法,研发新型多功能硼药是提高 BNCT 疗效的关键. 本研究通过对 10 B 4 C 纳米 颗粒进行表面化学修饰制备了一种新型多功能纳米硼药. 首先在 10 B 4 C 纳米颗粒 表面接枝超支化聚丙三醇(PG),然后通过 pH 敏感的腙键偶联阿霉素(DOX),得 到纳米硼药 10 B 4 C-PG-DOX. PG 层的高亲水性使 10 B 4 C-PG-DOX 在水溶液中具有 良好的分散性和稳定性;而 DOX 单元的引入使 10 B 4 C-PG-DOX 带有正电荷并赋 予纳米颗粒一定的亲脂性,从而更容易被肿瘤细胞内吞. 当 10 B 4 C-PG-DOX 的浓 度为 10 μg 10 B/mL 时,平均每个 4T1 小鼠乳腺癌细胞中 10 B 原子数高达(4.92 ± 0.36) × 10 11 个. 10 B 4 C-PG-DOX 进入 4T1 细胞后,主要分布在溶酶体中,而溶酶 体的酸性环境有利于腙键断裂并释放 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Dai et al reported the in vitro study result of the folate receptor-mediated boron-10 containing carbon nanoparticles as potential delivery vehicles for BNCT of nonfunctional pituitary adenomas [ 45 ]. Zhang et al reported the preparation of doxorubicin-conjugated 10 B 4 C nanoparticles, which could be used to combine BNCT and chemotherapy [ 46 ]. Zhang et al reported the preparation of a chitosan-lactobionic acid-thioctic acid-modified hollow mesoporous silica composite loaded with carborane (HMSN-S-S-CS-LA-TA) and its therapeutic effect on hepatocellular carcinoma [ 47 ].…”
Section: Recent Development and The Challengesmentioning
confidence: 99%
“…Dai et al reported the in vitro study result of the folate receptor-mediated boron-10 containing carbon nanoparticles as potential delivery vehicles for BNCT of nonfunctional pituitary adenomas [ 45 ]. Zhang et al reported the preparation of doxorubicin-conjugated 10 B 4 C nanoparticles, which could be used to combine BNCT and chemotherapy [ 46 ]. Zhang et al reported the preparation of a chitosan-lactobionic acid-thioctic acid-modified hollow mesoporous silica composite loaded with carborane (HMSN-S-S-CS-LA-TA) and its therapeutic effect on hepatocellular carcinoma [ 47 ].…”
Section: Recent Development and The Challengesmentioning
confidence: 99%